ANALISIS PELAKSANAAN SISTEM PENGENDALIAN INTERNAL PADA INSPEKTORAT KABUPATEN MINAHASA UTARA - Kapoh, Octaviani M.; Ilat, Ventje; Warongan, Jessy D.L (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Every organization, whether private or government, is obliged to carry out control activities, as one of the efforts made in achieving organizational goals that have been established. Related to the government sector in Indonesia, the current approach of internal control system is the Sistem Pengendalian Intern Pemerintah (SPIP) covering environmental elements of control, risk assessment, control activities, information and communication, and monitoring. The object of this research is Inspektorat Kabupaten Minahasa Utara. As the research method used is descriptive qualitative. That results of this study can be concluded that the implementation of internal control system in the Inspektorat Kabupaten Minahasa Utara has been in accordance with the elements in the Internal Control System that has been established by the government based on Government Regulation No. 60 of 2008, so as to show the achievment of Inspektorat Kabupaten Minahasa Utara performance in 2016 has increased and can be said to be effective.Keywords: Government Internal Control System, Control Environment, Risk Assessment, Control Activities, Information and Communication, Monitoring